Pancreatic Cancer: Alarm for Survival - Felix Aloysius Budimutiar; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2019)
Pancreatic cancer is one of the deadliest and a highly aggressive cancer. Its incidence and mortality are highest in developed countries. However, in Asia-Pacific region, the incidence and mortality rate of pancreatic cancer are also on increasing trend nowadays. Pancreatic cancer incidence rates increase with older age, the highest in the 7th and 8th decades. Clinical presentation of pancreatic cancer are usually non-specific, largely dependent on tumour size and location, with most patients experience symptoms already late in the disease. Computed tomography is considered the method of choice for diagnosis and staging of pancreatic cancer. Management for pancreatic cancer include surgical resection, radiotherapy, chemotherapy. Only surgical resection considered the potentially curative treatment for pancreatic cancer. Unfortunately, a lot of patients present with disease that is not surgically resectable. Prognosis for pancreatic cancer is very poor, despite surgery in resectable patients. The overall five-year survival rate is about less than 5%